Protective Buffering by Service Members During Military Deployments: Associations with Psychological Distress and Relationship Functioning. Issue 2 (7th January 2019) - Carter, Sarah P.; Renshaw, Keith D.; Curby, Timothy W.; Allen, Elizabeth S.; Markman, Howard J.; Stanley, Scott M.
Abstract : To shield a romantic partner from potential distress due to stressors occurring during deployment, service members (SMs) may engage in protective buffering, or withholding information or concerns from a romantic partner. This study utilized data from 54 couples collected before, during, and after a military deployment to assess whether SMs engaged in protective buffering while deployed and the possible associations between buffering and psychological, relationship, and contextual factors. Only 2% of SMs indicated never engaging in protective buffering during a deployment. In bivariate analyses, only partners' psychological distress prior to deployment was significantly associated (negatively) with protective buffering. In multilevel models with time nested within individuals, and individuals nested within couples, higher buffering was associated with less partner distress during deployment, but was also associated with higher SM distress both during and after deployment. In these multilevel models, protective buffering was not significantly associated with SM or partner marital satisfaction. Abstract : Para proteger a una pareja romántica del posible distrés debido a factores desencadenantes de estrés que se producen durante la movilización militar, los miembros de las fuerzas armadas pueden adoptar una conducta de atenuación protectora u ocultar información o preocupaciones a una pareja romántica. El presente estudio utilizó datos de 54 parejas recopilados antes, durante y después de una movilización militar para evaluar si los miembros de las fuerzas armadas adoptaron una conducta de atenuación protectora mientras estaban movilizados y las posibles asociaciones entre la atenuación y los factores psicológicos, relacionales y contextuales. Solo el 2% de los miembros de las fuerzas armadas indicaron no haber adoptado nunca una conducta de atenuación protectora durante una movilización militar. En los análisis bivariables, solo el distrés psicológico de las parejas antes de la movilización militar estuvo asociado considerablemente (negativamente) con la atenuación protectora. En los modelos multinivel, con el tiempo localizado dentro de las personas y las personas localizadas dentro de las parejas, una mayor atenuación estuvo asociada con menos distrés de la pareja durante la movilización militar, pero también estuvo asociada con un mayor distrés de los miembros de las fuerzas armadas tanto durante como después de la movilización militar. En estos modelos multinivel, la atenuación protectora no estuvo asociada de forma significativa con la satisfacción conyugal de la pareja o del miembro de las fuerzas armadas. Abstract : 在服兵役期间, 为了保护情侣中的一方免受多种紧张因素引起的潜在痛苦的影响, 为国服兵役的军人们可能采取保护性的缓冲策略, 也就是向伴侣隐瞒一定的信息或不告知可能引起担忧的事情。本研究搜集了54对夫妇情侣在军事任务派遣之前、之中、之后的数据用来评估服役人员是否在服役期间采用了保护性缓冲策略, 以及隐瞒一些事情与心理, 关系和环境因素之间的可能的相互关联性。只有2%的服役人员表示从来没有在兵役期间使用过保护性缓冲策略。在双变量分析中, 只有在服役前, 情侣的压力和保护性缓冲有非常大地负关联。在多等级的模型即服役时间、个人和情侣关系的两两相互关系中, 服役期间若隐瞒的事情越多, 伴侣的痛苦越小, 不过服役军人本人在服役期间和结束之后的痛苦相应会越高。在这些多水平的模型中, 保护性缓冲策略和服役人员及其伴侣对婚姻的满意度并没有很大相关性。